GDNF Stimulates Rod Photoreceptors and Dopaminergic Amacrine Cells in Chicken Retinal Reaggregates - Volpert, Katja N; Rothermel, Andree; Layer, Paul G (Investigative ophthalmology & visual science, 2007)
To investigate the role(s) of glial cell line-derived neurotrophic factor (GDNF) on expression of rod photoreceptor and dopaminergic amacrine cell-specific genes in an in vitro reaggregate model of the chick retina. Retinal reaggregates derived from embryonic day (E)6 chicks (rosetted spheroids) were supplemented with 50 ng/mL GDNF, or, alternatively, endogenous GDNF expression was downregulated by transient transfection of spheroids with a pCMS-EGFP[GDNF] antisense vector. Using mainly semiquantitative RT-PCR analyses, expression of rhodopsin, four separate opsins, and tyrosine hydroxylase (THase) was analyzed after either treatment. Supplementation with GDNF accelerated rhodopsin mRNA expression and sustained it at an increased level, in contrast to untreated control subjects, where rhodopsin mRNA levels were lower and unmaintained. Expression of red, green, blue, and violet opsins were unaffected. Under these conditions, GDNF also massively increased the expression of tyrosine hydroxylase, the rate-limiting enzyme in the synthesis of dopamine. The expression of endogenous GDNF was blocked in spheroids by using antisense transfections, which resulted in both a significant decrease in rhodopsin mRNA expression and a complete suppression of THase expression, as determined by RT-PCR, Western blot analysis, and immunocytochemistry. GDNF supports expression of both rhodopsin and THase in vitro, two critical molecules involved in the production of rod photoreceptors and dopaminergic amacrine cells, respectively; however, the presence of GDNF does not affect cone production and survival.